Bebês com sequência de Pierre Robin: saúde mental materna e interação mãe-bebê - Nardi, Camila Guedes De Azevedo; Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Melchiori, Lígia Ebner [UNESP]; Salgado, Manoel Henrique [UNESP]; Tavano, Lilian D'aquino (Programa de Pós-Graduação em Psicologia, Pontifícia Universidade Católica de Campinas, 2015)
The aim of this study was to evaluate maternal stress and anxiety and the quality of interaction of 10 mothers and their 0-3-month-old babies with Pierre Robin Sequence hospitalized in a university hospital. We used the Inventory of Stress Symptoms for Adults to evaluate stress and the State-Trait Anxiety Inventory to assess anxiety of the mothers, and a protocol to assess the recording of the mother-infant interaction. The results showed high levels of maternal stress and anxiety. A statistically significant inverse relationship was found: the higher the maternal anxiety and stress, the lower was the mother-infant interaction. The results indicate that work needs to be done to minimize the anxiety and stress of mothers with inpatient babies in order to encourage interaction.

Este estudo pretendeu avaliar o estresse e ansiedade materna, bem como a qualidade da interação de dez mães e seus bebês, de zero a três meses, com Sequência de Pierre Robin, internados em um hospital universitário. Utilizou-se uma escala e um inventário para avaliação do estresse e da ansiedade maternos e um protocolo para avaliação da filmagem da interação mãe-bebê. Os resultados apontaram altos níveis de estresse e ansiedade maternos. Foi encontrada uma relação inversa estatisticamente significativa: quanto maior a ansiedade e o estresse materno, menor a sintonia de interação da díade mãe-bebê. Os resultados indicam a necessidade de um trabalho que minimize a ansiedade e o estresse de mães com bebês internados, favorecendo a interação.
Infants with Pierre Robin sequence: maternal mental health and mother-infant interaction
Keywords: Anxiety; Stress; Mother-child relations; Ansiedade materna; Estresse materno; Relações mãe-criança